2021
DOI: 10.1002/cpt.2502
|View full text |Cite
|
Sign up to set email alerts
|

The PHARMACOM‐EPI Framework for Integrating Pharmacometric Modelling Into Pharmacoepidemiological Research Using Real‐World Data: Application to Assess Death Associated With Valproate

Abstract: In pharmacoepidemiology, it is usually expected that the observed association should be directly or indirectly related to the pharmacological effects of the drug/s under investigation. Pharmacological effects are, in turn, strongly connected to the pharmacokinetic and pharmacodynamic properties of a drug, which can be characterized and investigated using pharmacometric models. Recently, the use of pharmacometrics has been proposed to provide pharmacological substantiation of pharmacoepidemiological findings de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 92 publications
2
16
0
Order By: Relevance
“…We showed that in older patients with epilepsy the LSTM neural network had better predictive performance compared with a traditional pharmacometric model of valproate previously determined to have the highest accuracy in our external evaluation study. 1 Such better performance is expected and shown by others in clinical trials. 3,9 We believe that our results are mostly driven by four reasons.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…We showed that in older patients with epilepsy the LSTM neural network had better predictive performance compared with a traditional pharmacometric model of valproate previously determined to have the highest accuracy in our external evaluation study. 1 Such better performance is expected and shown by others in clinical trials. 3,9 We believe that our results are mostly driven by four reasons.…”
Section: Discussionmentioning
confidence: 63%
“…15 Second, as machine learning can incorporate high-dimensional data and describe nonlinear relationships between variables and response, 16 artificial neural networks can better explain the variability of plasma concentration between patients. Third, populations on which various pharmacometric models have been developed may differ from the real-world population, as also outlined in our recent study, 1 and thus it is expected that when applied to the realworld population such models may not perform well. 17 This was shown in our previous study, where external evaluation results were poor, 1 as well as by other external evaluation studies.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations